Hubungan Pengetahuan Sikap dan Dukungan Suami Terhadap Pemeriksaan Inspeksi Visual Asam Asetatdi Puskesmas Muara Enim - Ferra Puspa Sari; Erma Puspita Sari; Hasbiah Hasbiah; Eka Rahmawati (Universitas Batanghari Jambi, 2022)
Cervical cancer is a kind of malignant tumor which touches the surface layer (epithelium) of a cervix. This study was aimed to find out the simultaneous correlation between knowledge, attitude and husband’s support with the visual inspection with acetic acid (VIA) at Muara Enim Public Health Center year 2021. This study is a quantitative study applying survey analytical design using cross sectional approach. The population of this study was taken from all couples of their reproductive age who visited VIA polyclinic during August 2021. The samples of this study were 35 respondents who were taken by applying accidental sampling method in which the data were collected using questionnaires. Based on the result of bivariate analysis, it was found out that there was no correlation between knowledge and visual inspection with acetic acid (VIA). Those who had good knowledge and wanted to have VIA were 82.9%. Chi-square test showed (ρ value = 0.117). There was a correlation between attitude and visual inspection with acetic acid (VIA). Those who had positive attitude and wanted to have VIA were 65.7%. Chi-square test showed (ρ value = 0.001). There was a correlation between husband’s support and visual inspection with acetic acid (VIA). Those who got the support from husband and wanted to have VIA were 71.4%. Chi-square test showed (ρ value = 0.003). It can be concluded that there was no simultaneous correlation between attitude and husband’s supportwith the visual inspection with acetic acid (VIA) at Muara Enim Public Health Center year 2021. It is suggested that health workers improve their service, especially when dealing with visual inspection with acetic acid (VIA) and monitor the incidence of cervix cancer so it can decrease the number of mothers’ mortality caused by cervix cancer in Indonesia.